Evaluation of Peripheral Arterial Disease in Patients Presenting with Diabetic Foot Ulcer to Endocrine Clinic - Khalid Usman, Salman Khan, Hamza Muhammad, Tahir Ghaffar, Hajra Tariq, Faiz Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Diabetes mellitus is an increase in blood glucose levels results in altered fat, protein metabolism, and carbohydrate which leads to cardiac, eye, nervous system dysfunction, and kidney. The major cause of hospitalizations in patients with diabetes mellitus (DM) is diabetic foot ulcers (DFU). The purpose of the present study was to evaluate the peripheral arterial disease in diabetic foot ulcer patients presented to endocrine clinic. Patients and Methods: This descriptive cross-sectional study was carried out on 206 diabetic foot ulcers patients presented to the endocrine clinic in Peshawar from January 2021 to December 2022. Patients were enrolled after taking written informed consent from each individual. Patient’s details such as gender, age, peripheral artery disease (PAD), diabetes types, heart failure, wound size, diabetes duration, end-stage renal disease, DFU history, prior history of amputation, and peripheral neuropathy were recorded. Angiography and revascularization may be required if arterial Doppler ultrasound confirmed PAD. Additionally, wound debridement and topical dressings were applied. In the treatment of wound ischemia, pentoxifylline, and calcium blockers were recommended along with diabetes control procedures and appropriate antibiotics. SPSS version 27 was used for data analysis. Results: Of the total 206 DFU patients, there were 142 (68.9%) male and 64 (31.1%) females. The prevalence of peripheral artery disease (PAD) was 58.3% (n=120). Age-wise distribution of patients were as follows: 31 (15%) in 25-45 years, 107 (52%) in 46-65 years, 60 (29.1%) in 66-85 years, and 8 (3.9%) >85 years. Out of 206 DFU patients, the prevalence of type-I diabetes mellitus and type-II diabetes mellitus was 8 (3.9%) and 198 (96.1%) respectively. PAD prevalence was significantly associated with Type 2 diabetes. The incidence of PAD in plantar foot, non-plantar foot, and heel was 66 (55%), 42 (35%), and 12 (10%) respectively among 120 cases. Out of 206 DFU cases, the incidence of peripheral neuropathy, DFU history, amputation history, heart failure, and chronic renal failure was 142 (68.9%), 104 (50.5%), 54 (26.2%), 46 (22.3%), and 42 (20.4%) respectively. Conclusion: The present study concluded that the prevalence of peripheral artery disease (PAD) was 58.3% among diabetic foot ulcers. Results indicate that DFU and PAD are significantly related. It has been found that male patients with DFU were more likely to suffer from PAD as compared to women with statistically insignificant association. Keywords: Peripheral artery disease, diabetic foot ulcers, type-II diabetes mellitus